The perception of injury risk and prevention among football players: A systematic review - Cardoso-Marinho, Beatriz; Barbosa, Ana; Bolling, Caroline; Marques, José Pedro; Figueiredo, Pedro; Brito, João (Frontiers in Sports and Active Living, 2022)
Football is associated with a certain risk of injury, leading to short- and long-term health consequences. However, the perception of football players about injury risk and prevention strategies is poorly documented. The present article reviewed the literature about perceptions, beliefs, attitudes and knowledge toward injury risk and prevention strategies in football players. An electronic search was performed in PubMed, Scopus, Web of Science, and APA PsychINFO until July 2022. Studies were eligible if they included the perceptions, beliefs, attitudes, and knowledge about injury risk and prevention in football players from any competitive level. The risk of bias was assessed in included studies using the Joanna Briggs Institute critical appraisal checklist. A total of 14 studies were included. Most football players agreed that their risk of injury is high and prevention strategies are important, however they do not intend to use some of these strategies. The most frequent perceived injury risk factors were low muscle strength, lack of physical fitness, fatigue, excessive training and type and condition of surfaces. The most frequent perceived injury prevention factors were warm-up, workload monitoring and strength and conditioning training. It is essential to acknowledge perceived injury risk factors, as well as a better understanding of how coaching and medical departments' perceptions match with players' perceptions, and a modification in the perceptions of the several stakeholders at different levels of action.